Francis Bacon's New Atlantis New Interdisciplinary Essays - Price, Bronwen (Manchester University Press, 2003)
The New Atlantis has fired the imaginations of its readers since its original appearance in 1627. Often regarded as the apotheosis of Bacon's ideas through its depiction of an advanced 'scientific' society, it is also read as a seminal work of science fiction. Standing at the threshold of early modern culture, this key text incorporates the practical and visionary, utility and utopia. This volume of eight new essays by leading scholars provides a stimulating dialogue between a range of critical perspectives. Encompassing the fields of cultural history, history of science, literature and politics, the collection explores The New Atlantis' complex location within Bacon's oeuvre and its negotiations with cultural debates of the past and present. Contributors consider the book's use of rhetoric, its narrative contexts, its political and ethical implications, its relation to the natural knowledge of the period, and the function of miracles in New Atlantan society. The politics of colonialism and Jewish toleration, its complex representation of gender, and the role and politics of censorship are also explored. This volume will be the ideal companion to Bacon's The New Atlantis and for all students of literature, politics, history, cultural history and history of science.